Environmental spread of antibiotic molecules, antibiotic resistant bacteria and genes: jigsaw pieces of a public health problem - Silveira, Eduarda (2009)
o uso massivo de antibióticos na medicina humana e no ambiente de produção animal é responsável pela libertação no ambiente de resíduos contaminados por moléculas de antibióticos,bactérias resistentes e seus respectivos genes. condições particulares encontradas no ambiente podem promover a selecção e a persistência, por longos períodos de tempo,de microrganismos com uma capacidade extraordinária de participar em eventos genéticos de disseminação horizontal e recombinação, que melhoram as suas competências de adaptação e/ou colonização a vários hospedeiros, incluindo o Homem. A contaminação de diferentes nichos ambientais em várias regiões do globo pode colocar em risco o sucesso de medidas restritivas à disseminação de bactérias resistentes. A massive use of antibiotics in human medicine and in animal production setting is responsible for the release to the environment of waste products contaminated by antibiotic molecules, antibiotic resistant bacteria and/or their genes. particular conditions found in the environment might promote the selection and a long time persistence of microorganisms with an extraordinary ability to participate in genetic horizontal dissemination and recombination events, which might improve their adaptation and colonization skills to diverse settings, including the human one. the contamination of different environmental niches in several regions worldwide may undermine the success of the resistant bacteria containment measures.